Single‐band full‐duplex MAC protocol for distributed access networks. Issue 10 (1st July 2014) - Askari, Elaheh; Aïssa, Sonia
Abstract : Recent advances in wireless communications promised the realisation of a revolutionary technique, called full‐duplex (FD), which allows communication in both directions at the same time and over the same channel. However, the viability of FD in the physical layer requires the support of the MAC layer to fully spread the advantages of this technology to the whole wireless network. In this study, the authors introduce a distributed MAC protocol, termed distributed‐access FD MAC, suitable for multi‐hop communications whereby nodes are FD enabled. Using this protocol, a data packet can be forwarded by a number of nodes along a multi‐hop path with un‐contented access to the channel at each hop except for the head node. After detailing the specifications of this protocol, they establish a finite‐state discrete‐time Markov model to evaluate its performance. Using probabilistic mathematical methods, they derive important quantitative metrics such as path delay and throughput. Numerical results are provided and demonstrate the considerable improvement in network performance that the proposed protocol achieves compared with CSMA/CA half‐duplex access mechanism.